2022
DOI: 10.2196/40719
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Chatbot for Young Adults With Depressive Symptoms During the COVID-19 Pandemic: Single-Blind, Three-Arm Randomized Controlled Trial

Abstract: Background Depression has a high prevalence among young adults, especially during the COVID-19 pandemic. However, mental health services remain scarce and underutilized worldwide. Mental health chatbots are a novel digital technology to provide fully automated interventions for depressive symptoms. Objective The purpose of this study was to test the clinical effectiveness and nonclinical performance of a cognitive behavioral therapy (CBT)–based mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 91 publications
0
39
0
Order By: Relevance
“…Certain studies claimed that CAIs can help users feel accompanied and understood [ 19 , 20 ]; several studies found that users establish therapeutic bonds with chatbots [ 21 - 24 ]; and other studies revealed some hazards associated with CAIs, including misunderstanding that may result in inefficient or even harmful interventions, a lack of crisis warning systems, and a lack of privacy protection [ 25 ]. An increasing number of CAIs have emerged in recent years, as the digital medical and mobile health fields have grown [ 26 ], solving and improving a larger range of mental health issues in addition to depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies claimed that CAIs can help users feel accompanied and understood [ 19 , 20 ]; several studies found that users establish therapeutic bonds with chatbots [ 21 - 24 ]; and other studies revealed some hazards associated with CAIs, including misunderstanding that may result in inefficient or even harmful interventions, a lack of crisis warning systems, and a lack of privacy protection [ 25 ]. An increasing number of CAIs have emerged in recent years, as the digital medical and mobile health fields have grown [ 26 ], solving and improving a larger range of mental health issues in addition to depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 25 studies, 19 were recently published (between 2020 and 2023) 8 10 , 12 , 26 40 . Studies were conducted predominantly in the US ( n = 12) 11 , 12 , 27 , 28 , 33 , 34 , 38 , 41 45 , followed by Europe ( n = 5) 10 , 26 , 29 , 32 , 35 , Asia ( n = 4) 9 , 31 , 36 , 39 , New Zealand ( n = 2) 37 , 40 , and Australia ( n = 1) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the dialog system underlying the process of conversation, almost half of automated CAs ( n = 12) employed natural language processing and machine learning to carry on an interaction 8 , 9 , 12 , 27 , 30 , 31 , 34 , 38 , 39 , 41 , 43 , 45 . Predefined dialog or interactions assembled, and matched to the user input in a dynamic manner was used in 10 studies 10 , 11 , 26 , 28 , 29 , 32 , 33 , 35 , 40 , 44 , while 3 used a mixed dialog system 36 , 37 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Other disciplines, such as psychology, have already proven that chatbots are an effective way to complete patient anamneses in advance online in an easy and accessible manner. 6 Additional studies with larger patient groups are needed to further explore the potential of chatbots in allergology and beyond.…”
Section: F I G U R Ementioning
confidence: 99%